2017
DOI: 10.21608/jssae.2017.38086
|View full text |Cite
|
Sign up to set email alerts
|

Water Productivity of Wheat Crop as Affected by Different Sowing Dates and Deficit Irrigation Treatments

Abstract: Climate change scenarios require reconsidering different agricultural practices including sowing dates and irrigation intervals. For this purpose, a field experiment was carried out at the Agricultural Research Farm of Sakha Agricultural Research Station, Kafr-Elsheikh Governorate during the successive winter seasons 2013/2014 and 2014/2015 to investigate the impact of deficit water irrigation and sowing dates on wheat crop productivity(Triticum aestivum L.). The experimental site located at latitude of 30˚: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…The obtained results showed a small increase in DU values in the second season compared to the first season. The obtained results were similar to those reported by Taha (2018) and Taha and Khalifa (2022), who indicated that the DU values measured for different fruit trees using a drip system with a lateral length of 24 m were 89% and 90% in the first and second seasons, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The obtained results showed a small increase in DU values in the second season compared to the first season. The obtained results were similar to those reported by Taha (2018) and Taha and Khalifa (2022), who indicated that the DU values measured for different fruit trees using a drip system with a lateral length of 24 m were 89% and 90% in the first and second seasons, respectively.…”
Section: Resultssupporting
confidence: 90%
“…This may be due that originated from more suitable weather conditions during this period, which led to encouragement germination, particularly day shortage, low temperatures and light intensity with suitable growth period of wheat plants vegetative growth. These results are in line with those obtained by Farooq et al (2016), Taha et al (2017), El-Hag Dalia (2019 and Tahir et al (2019).…”
Section: Yield Componentssupporting
confidence: 93%
“…Choosing the right sowing dates can maximize the outcomes of the interaction between genotype and environment, thus increasing grain yield and baking quality of wheat (Silva et al, 2014). Sowing of wheat during November gave the highest values for each of the yield and its components, while the late sowing in early or mid-December led to a decrease these values and an increase in the grain content of protein (El-Hag Dalia, 2019;El-Sayed et al, 2018;Farooq et al, 2016;Taha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, enough irrigation water may help the plant to absorb its need for water and nutrients as well as increased the grain-filling period (El-Hendawy, 2016). Drought stress leads to decreased fresh and dry matter production (Gora et al, 2022), total chlorophyll, and photosynthesis (Shalaby et al, 2020), and thus reduced the spike length (Kanwal et al, 2020), flag leaf area (El-Sarag and Ismaeil, 2013), grains weight spike -1 and 1000-grain weight (Al-Zahy et al, 2020 andKotb et al, 2021), grain yield (El-Nagar and EL-Gohary, 2022), and increased WUE (Taha et al, 2017). Xu et al (2016) cleared that the increase in WUE was produced from 60 mm water applied at elongation, attaining a relatively high grain yield, whereas enough irrigation with180 mm water applied increased grain yield but decreased WUE.…”
Section: Effect Of Irrigation Intervalsmentioning
confidence: 99%